Production and operations management 00/01 - Shukla, P. K. (U.S.A Mcgraw-Hill College, 1999)
This anthology provides access to carefully selected articles from such sources as "Production and Inventory Management Journal", "Forbes", "Fortune", "National Productivity Review" and "Business Week". The readings cover performance improvement, quality, human resources management for productivity, forecasting and product design, capacity, location, logistics, and layout planning, inventory and supply-chain management, and emerging trends.
Keywords: management